CONGENITAL ISOLATED BILATERAL SOFT TISSUE SYNGNATHIA IN A 4-DAY OLD BABY BOY - Zalan, Abul Khair; Zubairy, Khadeejah Khalil; Niazi, Manahil; Zaman, Hira; Maxood, Anser; Gul, Anika (Journal of Ayub Medical College Abbottabad, 2021)
Congenital maxillomandibular syngnathia is characterized by fusion of jaws. Depending on the severity, it has a wide range of clinical presentations. It can be complete /incomplete and may be unilateral or bilateral. Primary concern in such patients is maintenance of airway and feeding difficulties. Therefore, early recognition and management is important to reduce nutritional, feeding, airway difficulties and growth-related problems in such new-borns. This case report presents a case of syngnathia in a 4-day infant with bilateral fusion of maxilla and mandible, leaving a small anterior portion. Early intervention was planned and the fusion was released to facilitate feeding. Good mouth opening was seen on 1week follow-up. Keywords: Congenital; Maxillomandibular fusion; Syngnathia; Synechiae